Childhood Injuries; Educational and Forensic Dimension - Kurt, Makbule; Pakiş, Işıl (The Bulletin of Legal Medicine, 2020)
Childhood is a period in which the awareness of self-protection against hazards has not yet developed due to the child's curiosity to explore and its mobile structure, therefore, it is open to trauma. On the other hand, child abuse and neglect affect children of all ages, races and income levels is an important public health problem that can be encountered in this age group. Teachers are in a relationship with children and their families in the community and play an important role in understanding, reporting and preventing child abuse. The first step to take when helping or starting to help a child exposed to abuse or neglect is to know the signs and symptoms of abuse. The most important approach; child abuse should be suspected. Here, it is very important to correctly identify the findings of accident-related injuries and the injuries associated with abuse and to manage the process correctly in children that are suspected of abuse. The aim of the study is to classify the findings related to childhood child abuse and the findings related to childhood accidents and draw attention to the points that need to be observed correctly.
Keywords: child abuse; accident; teacher